A Novel Bacterial Artificial Chromosome-Transgenic Podoplanin–Cre Mouse Targets Lymphoid Organ Stromal Cells in vivo - Onder, Lucas; Scandella, Elke; Chai, Qian; Firner, Sonj; Mayer, Chrisitan; Sparwasser, Tim; Thiel, Volker; Rülicke, Thomas; Ludewig, Burkhard (Frontiers in Immunology, 2011)
Stromal cells provide the structural foundation of secondary lymphoid organs (SLOs), and regulate leukocyte access and cell migration within the different compartments of spleen and lymph nodes. Furthermore, several stromal cell subsets have been implied in shaping of T cell responses through direct presentation of antigen. Despite significant gain of knowledge on the biology of different SLO-resident stromal cell subsets, their molecular and functional characterization has remained incomplete. To address this need, we have generated a bacterial artificial chromosome (BAC)-transgenic mouse model that utilizes the podoplanin (pdpn) promoter to express the Cre-recombinase exclusively in stromal cells of SLOs. The characterization of the pdpn:Cre mouse revealed transgene expression in distinct subsets of fibroblastic reticular cells (FRCs) and lymphatic endothelial cells (LECs) in lymph nodes (LNs). Furthermore, the transgene facilitated the identification of a novel splenic perivascular stromal cell subpopulation that forms web-like structures around central arterioles. Assessment of the in vivo antigen presenting function of the genetically tagged stromal cells in pdpn:Cre mice revealed activation of both MHC I and II-restricted TCR transgenic T cells. Taken together, stromal pdpn:Cre-recombinase expression is well-suited to dissect antigen presentation by FRCs and LECs in LNs and by the novel splenic perivascular stromal cell population.